Treatment of metal cutting fluid wastewater over Pt/Al2O3 and Ru/Al2O3 in supercritical water medium - Rahimov, Murad; Akgun, Mesut (ELSEVIER, 2022)
Metal cutting fluids (MCFs) are used in the manufacture of metal parts and the machining industry for lubrication and cooling. They are mainly composed of water and oils but to increase efficiency and life of MCF, various additives such as antioxidants, antifoams, anti-corrosives, biocides, fungicides, etc. are also added to MCFs. The complex composition of MCFs make it hazardous to the environment, so treatment before disposal becomes necessary. In this study, the catalytic treatment of metal cutting fluid wastewater by SCWO using Ru/Al2O3 and Pt/Al2O3 catalysts was investigated. The effects of temperature (400-600 degrees C), pressure (20-35 MPa), and residence time (60-150 s) on the treatment efficiency based on total organic carbon (TOC) removal were investigated in the presence of Ru/Al2O3 and Pt/Al2O3 catalysts. It was observed that the treatment efficiency increased sharply in the temperature range of 450-500 degrees C, a residence time of 60 s, and a pressure of 25 MPa. At 600 degrees C, conversion of more than 93% was obtained for both catalysts. A treatment efficiency of 99% was achieved when hydrogen peroxide as oxidant was used at a ratio of 2:1 to the initial concentration of metal cutting fluid wastewater (MCFW). Overall, it was found that the use of a Ru/Al2O3 catalyst gave a higher treatment efficiency than a Pt/Al2O3 catalyst. Using the obtained data, a reaction kinetic model was constructed and a correlation coefficient of more than 95% was obtained when comparing the experimental data and the model data.
Keywords: Metal cutting fluids; Wastewater treatment; Pt/Al2O3; Ru/Al2O3; Supercritical water; METALWORKING FLUIDS; KINETIC-MODEL; OXIDATION; OIL; COAGULATION; EMULSION; BIODEGRADATION; PURIFICATION; TEMPERATURE; PERFORMANCE; Engineering; Water Resources